1993
DOI: 10.1007/bf00157392
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the epidemiology of child infections in the Bari area (South Italy) VII. Epidemiology of Epstein-Barr virus infections

Abstract: Serological patterns against Epstein-Barr virus (EBV) specific antigens were determined in 3732 healthy babies and children aged 0-10 years living in the Bari area (South Italy). IgG antibodies against EBV capsid antigen (VCA) were found in 2713 subjects (72.7%). Seropositivity rates, high in the first semester of life (83.8%), declined between 6 and 12 months (65.6%) and even further between 1 and 2 years (43.8%). After 2 years the frequency of positive children rose progressively reaching steady levels betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…This pattern has also been observed in other studies and is due to preexisting maternal antibodies active in infants under six-months-old (Leogrande et al, 1993). Longitudinal serological data have shown that maternal anti-EBV protection usually lasts for 3-4 months (Biggar et al, 1978;Chan et al, 2001).…”
Section: Discussionsupporting
confidence: 84%
“…This pattern has also been observed in other studies and is due to preexisting maternal antibodies active in infants under six-months-old (Leogrande et al, 1993). Longitudinal serological data have shown that maternal anti-EBV protection usually lasts for 3-4 months (Biggar et al, 1978;Chan et al, 2001).…”
Section: Discussionsupporting
confidence: 84%
“…Another coincidence between EBV and gastroschisis is noted in southern Italy. There, a relatively high rate of EBV seropositivity (80%) was observed in 5-to 7-year-old children (Leogrande and Jirillo, 1993), which is almost double what was observed in the United Kingdom during the same time period . Compared with most other parts of Europe, the prevalence of gastroschisis is low in southern Italy (<1 per 10,000 births) and has not been increasing (Calzolari et al, 1993), perhaps owing to lower rates of EBV infection in childbearing women.…”
Section: Resultsmentioning
confidence: 76%
“…Genetics and family environment could contribute to the acquisition of EBV infection, as suggested by a study from Minnesota in which EBV antibodies prevalence was detected and correlated between brothers [18]. Also, in Southern Italy, EBV PI occurs at an early age, as described in an epidemiological study conducted in Bari, which reported positive EBV IgG in patients >4 years old [19]. …”
Section: Discussionmentioning
confidence: 99%